PENGEMBANGAN MEDIA PEMBELAJARAN SPINNING WHEEL UNTUK MENINGKATKAN HASIL BELAJAR MATERI IPAS KELAS IV DI SD NEGERI PANDEAN LAMPER 02 - Annisa Barokatil Zulfah; Qoriati Mushafanah; Ferina Agustini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background that drives this research is the low understanding of fourth grade elementary school students regarding the material of plant body parts and their functions in learning natural and socialsciences (IPAS). The results of observations and interviews at SDN Pandean Lamper 02 showed that teachers did not adapt learning to the needs of students in using interesting teaching media during teaching and learning activities in class, because teachers only focused on the printed books used so that students were not interested and bored while learning. This type of research is research and development (R&D) with the ADDIE development model consisting of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of one teacher and 29 fourth grade students of SDN Pandean Lamper 02. The results of this study showed that the developed Spinning Wheel media was declared very suitable for use based on the assessment of media and material validators. Teachers and students gave very good responses, shown by enthusiasm during learning that the media facilitated understanding of IPAS material. Effectiveness testing through a comparison of pretest andposttest scores showed a significant increase in learning outcomes after the use of the Spinning Wheel media. This demonstrates that the Spinning Wheel media can create an interactive, enjoyable learning environment and increase student engagement. Suggestions include developing this media digitally or expanding the study to different materials and grade levels to achieve better results.